ENVIRONMENT L QUALITY OF THUY TRIEU LAGOON, I KHANH HOA PROVINCE - Vinh, Le Thi (Vietnam Journal of Marine Science and Technology, 2009)
Results ofinvestigations in 2005-2006 indicated that water quality ofThuyTrieu Lagoon was relatively good although concentrations of ammonia, nitrate, and phosphate were sometimes higher than the maximum allowable value regard to waters for I mariculture (70 j.lg/1 for NH3.rN; 100 j.lgll for NOrN; 15 j.lg/1 for POrP) and DO concentration was rarely below the minimum value of5 mg/1. The values ofparameters were rangedfrom 22. 2 to 45.2rng!lJor total suspended solids; 4.8- 7.40 mgllfor DO; 15.3- 37.3 mg/lfor COD; 0.3- 5.0 f.lgN/lfor N01 ; 44- 155 f.lgN/lfor N03 ; 0- 84 JLgN/lfor NH3.4; 3.6-25.6 j.lgP/lfor P04 ; 232- 146kl j.lgSi!lfor Si03; 436- 786 JlgN!lfor organic N; 27.5-44. 5 j.lgP/lfor organic P.For sediment quality, c6mtent oforganic matters was not high (organic Carbon from I 0.1 to 1.3 %; organic N from 710 to 1294 Jlglg and total P from 16. 3 to 716 j.lglg} , they were mainly terrigenous in origin.Environmental quality dfThuy Trieu Lagoon did not show big difference compared to studied results in the 2002-200Bperiod except for high concentration ofammonia in October, 2003 (maximum : 296 j.lgN/1)